2009
DOI: 10.1192/bjp.bp.107.040485
|View full text |Cite|
|
Sign up to set email alerts
|

Group psychoeducation for stabilised bipolar disorders: 5-year outcome of a randomised clinical trial

Abstract: Six-month group psychoeducation has long-lasting prophylactic effects in individuals with bipolar disorders. Group psychoeducation is the first psychological intervention showing such a long-term maintained efficacy in people with bipolar disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
173
1
32

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 327 publications
(209 citation statements)
references
References 24 publications
3
173
1
32
Order By: Relevance
“…The existing evidence base for group psychological treatments in preventing relapses for BD is inconsistent. The first trial of PEd in a group of people with BD, showed clinical and cost-effectiveness for all types of bipolar relapse (9)(10)(11). Generally however findings from previous trials of PEd have been heterogeneous in design, often involving a small number of participants and short follow-up periods.…”
Section: Introductionmentioning
confidence: 99%
“…The existing evidence base for group psychological treatments in preventing relapses for BD is inconsistent. The first trial of PEd in a group of people with BD, showed clinical and cost-effectiveness for all types of bipolar relapse (9)(10)(11). Generally however findings from previous trials of PEd have been heterogeneous in design, often involving a small number of participants and short follow-up periods.…”
Section: Introductionmentioning
confidence: 99%
“…These efforts have been traditionally supported by psychosocial treatments that are designed to increase practical knowledge about the illness and its management (e.g., group psychoeducation; Colom et al, 2009), as well as to improve interpersonal and coping skills (Frank et al, 2005). Although studies support the efficacy of these interventions, they are clearly insufficient in fully addressing the problem of psychosocial impairment in BD.…”
Section: Implications For Carementioning
confidence: 99%
“…These findings focused current efforts for improving psychosocial functioning in BD on reducing subsyndromal depressive symptoms (M. Bauer et al, 2009) and cognitive dysfunction (Bearden et al, 2011;Deckersbach et al, 2010;Martínez-Arán et al, 2011), as well as enhancing stress management and interpersonal skills (Frank et al, 2000;Martínez-Arán et al, 2011). The bulk of this research emphasizes pharmacological interventions (Nivoli et al, 2011), followed by psychosocial treatments, such as psychotherapy (Ball et al, 2006;Hollon & Ponniah, 2010;Miklowitz, George, Richards, Simoneau, & Suddath, 2003;Miklowitz et al, 2008) and psychoeducation (Colom et al, 2009), as well as cognitive (Deckersbach et al, 2010) and functional remediation (Martínez-Arán et al, 2011). More broadly, the current overall approach to improving psychosocial adjustment in BD focuses on changing internal factors, with less consideration given to reducing environmental barriers to functioning.…”
Section: Predictors Of Psychosocial Functioning In Bdmentioning
confidence: 99%
“…In a comparative study by Colom [23], a group of patients receiving standard treatment for bipolar disorder was compared with a group receiving psycho education additionally as an adjunctive therapy, for a 5 year follow-up period. It was reported that patients receiving adjunctive psycho-education therapy experienced fewer relapse and shorter periods with acute symptoms, and needed shorter hospital stay [23].…”
Section: Literature On the Use Of Psychotherapy For Bipolar Disordermentioning
confidence: 99%